Effect of Fermentation of Sweet Orange (Citrus sinensis) Fruit Peel on its Phytonutrients and the Performance of Broiler Starter - Oluremi, O.I.A.; Okafor, F.N.; Adenkola, A.Y.; Orayaga, K.T. (International Journal of Poultry Science, 2010)
A 5-week feeding trial to determine the effect of fermentation of sweet orange (Citrus sinensis) fruit peel on its maize replacement value in broiler starter diet was conducted. Sweet orange fruit peels were collected from peeled orange sellers and divided into three portions. The first portion was not fermented (SP0), while the second and third portions were fermented for 24hrs (SP24) and 48hrs (SP48), respectively. They were separately sun-dried, milled and samples screened and analyzed for phytonutrients. Four different diets namely the control (CD) and three test diets SP0D, SP24D and SP48D in which SP0, SP24D and SP48 replaced maize in the control diet (CD) at 30% level in that order were compounded. Seven-day old one hundred and twenty Anak 2000 broiler chicks were randomly assigned to these diet groups to evaluate their performance. There was a decrease in the concentration of each of oxalate, flavonoid, tannin, saponin and phytate detected in the peels as the duration of fermentation increased from 0 to 48hrs. Thirty percent replacement of maize by the fermented sweet orange fruit peel meal depressed body weight gain (p